2012
DOI: 10.1590/s1678-77572012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Peel bond strength of resilient liner modified by the addition of antimicrobial agents to denture base acrylic resin

Abstract: In order to prolong the clinical longevity of resilient denture relining materials and reduce plaque accumulation, incorporation of antimicrobial agents into these materials has been proposed. However, this addition may affect their properties.ObjectiveThis study evaluated the effect of the addition of antimicrobial agents into one soft liner (Soft Confort, Dencril) on its peel bond strength to one denture base (QC 20, Dentsply). Material and MethodsAcrylic specimens (n=9) were made (75x10x3 mm) and stored in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
(46 reference statements)
0
43
0
4
Order By: Relevance
“…Therefore, cohesive failures provide information related to the material strength rather than to the bond between materials. However, mixed and adhesive failures were observed in some specimens, indicating that the cohesive strength values of the lining materials and bond strength values to base resin were similar 40) . In shear bond strength testing, all MB specimens exhibited mixed failures, whereas the VS specimens and all of the experimental materials exhibited cohesive failures.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, cohesive failures provide information related to the material strength rather than to the bond between materials. However, mixed and adhesive failures were observed in some specimens, indicating that the cohesive strength values of the lining materials and bond strength values to base resin were similar 40) . In shear bond strength testing, all MB specimens exhibited mixed failures, whereas the VS specimens and all of the experimental materials exhibited cohesive failures.…”
Section: Discussionmentioning
confidence: 82%
“…2 According to the literature, this condition occurs in between 11% and 67% of denture wearers. [3][4][5] Local factors associated with dentures are also connected with denture stomatitis, such as the presence of a biofilm, [6][7][8][9] local trauma caused by dentures, 10 xerostomia, 11 continuous use of dentures, 12 and alteration in the salivary pH. 12 Soft denture liners, namely soft polymers, can be applied to the mucosal or fitting area of the dentures.…”
Section: Introductionmentioning
confidence: 99%
“…28 In a study of the antimycotic action of nystatin-impregnated soft denture lining materials and the influence of 8 an aqueous environment on the fungicidal characteristics, Truhlar et al 6 showed that doses of 1,000,000 U and 500,000 U were useful in maintaining the drug-leaching quantity above the minimum inhibitory concentration for antifungal action. Radnai et al 12 demonstrated that miconazole gel, combined with a Viscogel tissue conditioner, restricted the emergence of C.…”
mentioning
confidence: 99%
See 2 more Smart Citations